تعلم وتكلم : الكتاب الاول (Ta'allam wa takallam : al-kitab 1) - Abdul Maqsud, Hasan; Chik, Abdul Rahman; Hayaza , Abdul karim Awadh; Haji Hitam, Saidai (Language Centre, Universiti Brunei Darussalam, 2004)
Learn to speak Arabic language